Pretreatment human immunodeficiency virus type 1 (HIV-1) drug resistance in transmission clusters of the Cologne-Bonn region, Germany. (February 2019) - Stecher, M.; Chaillon, A.; Eis-Hübinger, A.M.; Lehmann, C.; Fätkenheuer, G.; Wasmuth, J.-C.; Knops, E.; Vehreschild, J.J.; Mehta, S.; Hoenigl, M.
Abstract: Objectives: In Germany, previous reports have demonstrated transmitted human immunodeficiency virus type 1 (HIV-1) drug-resistance mutations (DRM) in 11% of newly diagnosed individuals, highlighting the importance of drug-resistance screening before the initiation of antiretroviral therapy (ART). Here, we sought to understand the molecular epidemiology of HIV DRM transmission in the Cologne-Bonn region of Germany, given one of the highest rates of new HIV diagnoses in western Europe (13.7 per 100 000 habitants). Methods: We analysed 714 HIV-1 ART-naive infected individuals diagnosed at the University Hospitals Cologne and Bonn between 2001 and 2016. Screening for DRM was performed according to the Stanford University Genotypic Resistance Interpretation. Shared DRM were defined as any DRM present in genetically linked individuals (<1.5% genetic distance). Phylogenetic and network analyses were performed to infer putative relationships and shared DRM. Results: The prevalence of any DRM at time of diagnosis was 17.2% (123/714 participants). Genetic transmission network analyses showed comparable frequencies of DRM in clustering versus non-clustering individuals (17.1% (85/497) versus 17.5% (38/217)). The observed rate of DRM in the region was higher than previous reports 10.8% (87/809) (p < 0.001), revealing the need to reduce onward transmission in this area. Genetically linked individuals harbouring shared DRM were more likely to live in suburban areas (24/38) than in central Cologne (1/38) (p < 0.001). Conclusion: The rate of DRM was exceptionally high. Network analysis elucidated frequent cases of shared DRM among genetically linked individuals, revealing the potential spread of DRM and the need to prevent onward transmission of DRM in the Cologne-Bonn area.